New Insights into the Mechanism of Reduction of Tertiary Phosphine Oxides by Means of Phenylsilane. Issue 6 (27th July 2015) - Demchuk, Oleg M.; Jasiński, Radomir; Pietrusiewicz, K. Michał
ABSTRACT: The mechanism of the reduction of phosphine oxides by PhSiH3 was established on the basis of kinetic measurements and Density Functional Theory (DFT) calculations. In particular, it has been proved that the model reaction between tri‐n‐butylphosphine oxide and phenylsilane occurs via a nonpolar mechanism. The data presented herein allow prediction and verification of the applicability of the new reduction reagents and conditions for industrially attractive processes.